The effect of different levels of sodium bicarbonate in lambs'ration on growth performance - Behiç Coşkun; Şakir Doğan Tuncer; Mehmet Ali Tekeş; Ali Akmaz; Şeref İnal (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effects of different levels of sodium bicarbonate that was added into concentrate mixtures in 0.5 and 1 % on growth performance. In the experiment, 42 Akkaraman male lambs with 5.5—6 months old were used. The research works were conducted as 3 groups for the period of 56 days. The ration of the control group did not contain any sodium bicarbonate.